Mali : Sixth Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Modification of Performance Criteria and Augmentation of Access; Staff Report; Informational Annex; Statement by the Staff Representative; Statement by the Executive Director for Mali; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2011)
The Growth and Poverty Reduction Strategy Paper III (GPRS-III) will provide a framework for the government's economic, financial, and sectoral policies for the period 2012-17. All performance criteria (PC) and indicative targets through end-December were observed, except for the indicative target on priority spending, which was missed by a small margin. All measures subject to end-year structural benchmarks were observed except one, on which the authorities are making good progress. The authorities plan to continue implementing stability-oriented macroeconomic policies and growth-enhancing and poverty-reducing policies. The Millennium Development Goals (MDGs) were achieved.